2013
DOI: 10.1021/jp4007203
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Adsorption on Au(111) and Ag(111) Surfaces: Adsorbed Selenium and Selenide Films

Abstract: Results of a high resolution photoemission and electrochemistry study of Se adsorption on Au(111) and Ag(111) surfaces performed by immersion of pristine samples into an aqeuous solution of Na 2 Se are presented. Cyclic voltammetry on Au shows formation of selenium adsorbed species and the structures observed in reductive desorption are related to the atomic and polymeric species observed in XPS. In the case of Au(111) XPS spectra in the Se(3d) region indeed show two main features attributed to Se chemisorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 61 publications
5
52
0
Order By: Relevance
“…Photoelectron line Au 4f 5/2 is fitted to two components: one at (88.07 eV) corresponding to the metallic state of bulk Au(111) although slightly shifted than previously reported in the literature for Au(111), 46 tured gold surface. 47 Relative intensity of surface, Is, to bulk, Ib, component of Au 4f 5/2 line is 0.24, while their separation is 1.27 eV. Phoptoelectron line Au 4f 7/2 is also fitted to two components: one at (84.4 eV), and the shoulder at 83.9 eV, corresponding to bulk Au(111) and to restuctured surface atoms, respectively, are also slightly shifted compared to literature data, 47 most likely due to the previous exposure of the electrode to the ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoelectron line Au 4f 5/2 is fitted to two components: one at (88.07 eV) corresponding to the metallic state of bulk Au(111) although slightly shifted than previously reported in the literature for Au(111), 46 tured gold surface. 47 Relative intensity of surface, Is, to bulk, Ib, component of Au 4f 5/2 line is 0.24, while their separation is 1.27 eV. Phoptoelectron line Au 4f 7/2 is also fitted to two components: one at (84.4 eV), and the shoulder at 83.9 eV, corresponding to bulk Au(111) and to restuctured surface atoms, respectively, are also slightly shifted compared to literature data, 47 most likely due to the previous exposure of the electrode to the ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…47 Relative intensity of surface, Is, to bulk, Ib, component of Au 4f 5/2 line is 0.24, while their separation is 1.27 eV. Phoptoelectron line Au 4f 7/2 is also fitted to two components: one at (84.4 eV), and the shoulder at 83.9 eV, corresponding to bulk Au(111) and to restuctured surface atoms, respectively, are also slightly shifted compared to literature data, 47 most likely due to the previous exposure of the electrode to the ambient conditions. 48 Is/Ib ratio is 0.23, and their separation is 0.5 eV, slightly higher than reported earlier, 47 most likely due to the higher roughness of the initial Au(111), prepared electrochemically.…”
Section: Resultsmentioning
confidence: 99%
“…The assignment of the Au 4f components is not straightforward, particularly, since AuSe contains two sorts of Au atoms, the oxidation state of which is a matter of dispute [35][36][37][38][39][40][41][42][43][44][45]. The Au 4f 7/2 peaks at 84.0-84.4 eV reported for gold-gold selenide [39][40][41], gold-CdSe [44,45]), adlayers of Se or alkyl selenides at Au [45][46][47][48][49]59], etc., originate from Au 0 surfaces but not AuSe phases. In nanostructured AuSe with admixture of Au [42], the values of 83.7 eV and 84.9 eV have been found, along with Se 3d 5/2 line at 54.5 eV, and ascribed to Au 0 and Au + , respectively; nevertheless, the authors assert the mixed valence state of gold (Au + Au 3+ Se 2 ).…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Particularly, Cueva et al [45] have concluded from X-ray photoelectron spectroscopy (XPS) analysis that the shells deposited on CdSe NPs are most probably composed of AuSe or AuSeCl, which are instable and transform into dot-shaped Au 0 particles under the electron beam in Transmission electron microscopy (TEM). Several studies on adsorption of selenium [46,47] and alkylselenides on gold and Au NPs [48,49] have revealed no AuSe phases and, for example, demonstrated that alkylselenides replace alkylsulfides due to favored Au-Se bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Some other dimer,t rimer,a nd chain-like selenium structuresw ere also detected. [21,22] Selenium clusters generated through laser ablation (LA) of seleniumo rd etected in seleniumvapors have been reported. [23][24][25][26][27][28][29][30][31] The structure of selenium clusters has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%